The effect of dynamic mobilization exercises and therapeutic trunk exercises on superficial epaxial and hypaxial muscle activity in horses - L.M. Harrison; L.B. St. George; L.M. Goff; G. Nardese; T. Barnes; B. Ahern; A. Sole-Guitart (Journal of Equine Veterinary Science, 2026)

A data-driven standardised generalisable methodology to validate a large energy performance Certification dataset: A case of the application in Ireland - K. Raushan; T. Mac Uidhir; M. Llorens Salvador; B. Norton; C. Ahern (Energy and Buildings, 2024)

Correction to: Altered T cell infiltration and enrichment of leukocyte regulating pathways within aged skeletal muscle are associated with impaired muscle function following influenza infection - Spencer R. Keilich; Andreia N. Cadar; Darcy T. Ahern; Blake L. Torrance; Erica C. Lorenzo; Dominique E. Martin; Laura Haynes; Jenna M. Bartley (GeroScience, 2023)

Altered T cell infiltration and enrichment of leukocyte regulating pathways within aged skeletal muscle are associated impaired muscle function following influenza infection - Spencer R. Keilich; Andreia N. Cadar; Darcy T. Ahern; Blake L. Torrance; Erica C. Lorenzo; Dominique E. Martin; Laura Haynes; Jenna M. Bartley (GeroScience, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Nudging fisheries and aquaculture research towards food systems - Fiona A. Simmance; Philippa J. Cohen; Cindy Huchery; Sarah Sutcliffe; Sharon K. Suri; Xavier Tezzo; Shakuntala H. Thilsted; Peter Oosterveer; Cynthia McDougall; Molly Ahern; Sarah Freed; Kendra A. Byrd; et al. (Fish and Fisheries, 2022)
Food system is a powerful concept for understanding and responding to nutrition and sustainability challenges. Food systems integrate social, economic, environmental and health aspects of food production through to consumption. Aquatic foods are an essential part of food systems providing an accessible source of nutrition for millions of people. Yet, it is unclear to what degree research across diverse disciplines concerning aquatic foods has engaged food systems, and the value this concept has added. We conducted a systematic review of fisheries, aquaculture and aquatic food literature (2017–2019) to determine the following: the characteristics of this research; the food systems components and interrelations with which research engaged; and the insights generated on nutrition, justice, sustainability and climate change. Sixty five of the 88 reviewed articles focussed on production and supply chains, with 23 considering human nutrition. Only 13% of studies examined low‐ and middle‐income countries that are most vulnerable to undernutrition. One third of articles looked beyond finfish to other aquatic foods, which illuminated values of local knowledge systems and diverse foods for nutrition. When aggregated, reviewed articles examined the full range of food system drivers—biophysical and environmental (34%), demographic (24%) and socio‐cultural (27%)—but rarely examined interactions between drivers. Future research that examines a diversity of species in diets, system‐wide flows of nutrients, trade‐offs amongst objectives, and the nutritional needs of vulnerable social groups would be nudging closer to the ambitions of the food systems concept, which is necessary to address the global challenges of equity, nutrition and sustainability.

Human Immunodeficiency Virus Promotes Mitochondrial Toxicity - Summer J. Rozzi; Valeria Avdoshina; Jerel A. Fields; Margarita Trejo; Hoai T. Ton; Gerard P. Ahern; Italo Mocchetti (Neurotoxicity Research, 2017)

Can genetically based clines in plant defence explain greater herbivory at higher latitudes? - Daniel N. Anstett; Jeffrey R. Ahern; Julia Glinos; Nabanita Nawar; Juha‐Pekka Salminen; Marc T. J. Johnson (Ecology Letters, 2015)
Greater plant defence is predicted to evolve at lower latitudes in response to increased herbivore pressure. However, recent studies question the generality of this pattern. In this study, we tested for genetically based latitudinal clines in resistance to herbivores and underlying defence traits of Oenothera biennis . We grew plants from 137 populations from across the entire native range of O. biennis . Populations from lower latitudes showed greater resistance to multiple specialist and generalist herbivores. These patterns were associated with an increase in total phenolics at lower latitudes. A significant proportion of the phenolics were driven by the concentrations of two major ellagitannins, which exhibited opposing latitudinal clines. Our analyses suggest that these findings are unlikely to be explained by local adaptation of herbivore populations or genetic variation in phenology. Rather greater herbivory at high latitudes can be explained by latitudinal clines in the evolution of plant defences.